2020
DOI: 10.4018/ijvar.2020010103
|View full text |Cite
|
Sign up to set email alerts
|

An Immersive Tractor Application for Sustainability

Abstract: South Africa is currently addressing the issue of land reform. This research explores how immersive technology could serve as an intervention to avoid unintended consequences in the agricultural industry. This work used participatory design, a stage-based approach, and the SCRUM project management methodology to develop a novel tractor-based immersive technology mobile application. The tractor application developed serves to support novice farmers and learners alike, to learn about and test their skills on tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For example, Kumari and Sahu used the number of domain names and users to rank the world's Internet cities based on the global Internet map [7]. Mabiletsa et al used a Twitter security system cracking program to extract geographic coordinates and text data, combined with time-series models to analyze the keyword characteristics and distribution of Twitter posts in different cities, and found that only a few cities could provide the information needed for multiple cities [8]. Mayub et al analyzed the communication information of 25 million subscribers provided by Belgian cell phone operators, used the postal codes corresponding to subscribers' cell phone billing addresses to establish social networks, applied the gravity model to study the communication intensity, and finally obtained the communication links and hierarchy between cities [9].…”
Section: Related Workmentioning
confidence: 99%
“…For example, Kumari and Sahu used the number of domain names and users to rank the world's Internet cities based on the global Internet map [7]. Mabiletsa et al used a Twitter security system cracking program to extract geographic coordinates and text data, combined with time-series models to analyze the keyword characteristics and distribution of Twitter posts in different cities, and found that only a few cities could provide the information needed for multiple cities [8]. Mayub et al analyzed the communication information of 25 million subscribers provided by Belgian cell phone operators, used the postal codes corresponding to subscribers' cell phone billing addresses to establish social networks, applied the gravity model to study the communication intensity, and finally obtained the communication links and hierarchy between cities [9].…”
Section: Related Workmentioning
confidence: 99%